2012
DOI: 10.1890/110246
|View full text |Cite
|
Sign up to set email alerts
|

Is global ocean sprawl a cause of jellyfish blooms?

Abstract: jellyfish (Cnidaria, Scyphozoa) blooms appear to be increasing in both intensity and frequency in many coastal areas worldwide, due to multiple hypothesized anthropogenic stressors. Here, we propose that the proliferation of artificial structures-associated with (1) the exponential growth in shipping, aquaculture, and other coastal industries, and (2) coastal protection (collectively, "ocean sprawl")-provides habitat for jellyfish polyps and may be an important driver of the global increase in jellyfish blooms… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
177
0
5

Year Published

2013
2013
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 262 publications
(185 citation statements)
references
References 46 publications
3
177
0
5
Order By: Relevance
“…Such events have been observed annually in specific months, especially during the summer and school holidays. Recent studies have shown a correlation between the presence of cnidarians and global warming 5,12 . In 2008, São Luis registered its highest ever number of envenomations.…”
Section: A B C Dmentioning
confidence: 99%
“…Such events have been observed annually in specific months, especially during the summer and school holidays. Recent studies have shown a correlation between the presence of cnidarians and global warming 5,12 . In 2008, São Luis registered its highest ever number of envenomations.…”
Section: A B C Dmentioning
confidence: 99%
“…The alteration of the coastal habitat by human constructions, such as marinas, docks and breakwaters, provides further substrates for planula settlement and asexual reproduction of the sessile polyp stage (Holst & Jarms 2007;Purcell et al 2007;Duarte et al 2013). Moreover, the polyp stage of C. marsupialis, besides performing budding, may also retain after metamorphosis a small basal portion of regenerative tissue attached to the substrate, from where a new polyp can arise (Straehler-Pohl & Jarms 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Jellyfish blooms are a nuisance to local fisheries, tourism, and coastal power plant operations. Multiple explanations have been suggested as possible drivers of the increase of jellyfish blooms in coastal marine ecosystems, including the depletion of predators and competitors of jellyfish through overfishing, eutrophication of coastal waters, increasing numbers of artificial structures associated with coastal development, and climate change (Duarte et al 2013). Model results suggest that mutual competition and predation between large jellyfish and pelagic fish form positive feedback loops that contribute to jellyfish blooms in the East China Sea (Jiang et al 2008).…”
Section: Shift To Jellyfish-dominant Statesmentioning
confidence: 97%